The never-ending Quest for the Elites:New Approaches to the Study of Cemeteries and Social Organization - Durgun, Pınar (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
The Early Bronze Age (EBA) in Anatolia (3100/3000-2000 BCE.)[1] is considered a period of great transition when urban societies developed and when extramural cemeteries started to emerge. Western Anatolian sites like Troy and Külloba have yielded monumental walls, or architecturally distinct quarters. However none of these sites have yielded extramural cemeteries. Extramural cemeteries of the EBA are only associated with small-scale sites such as Karataş (southwest Anatolia) and Demircihöyük (northwest Anatolia) which have been referred to as “chiefdoms”. Labeling these non-urban sites as chiefdoms inevitably led to the quest of finding the chief in these cemeteries. As a result, certain burial types, and burials with grave goods of higher quantity and better quality have been used as evidence for wealth and status, hence the presence of ruling elites. In this paper I suggest different ways of making use of the archaeological data from cemeteries to understand the social organization without falling into the same social evolutionary pitfalls.[1] In this presentation when I refer to Anatolia, I will be referring to the central and western parts of the peninsula, not to eastern Anatolia which in the Early Bronze Age is culturally and economically closer to Northern Mesopotamia.